Yealand Manor School - Hartshorne, Susan Vipont (Quaker studies, 2007)
In 1939 a small group of Manchester Friends set up a school for Quaker children evacuated from the northern cities for the duration of the war. It was open from September 1939 to July 1944 and during this time 183 children, aged between three and twelve years, passed through the school. In addition a number of refugees, mainly Jewish children, came to the school. The maximum number at the school at any one time was 76. It was staffed almost entirely by volunteers. In this article I focus on several of the more unusual aspects of this school. These include the way it was set up and the reasons for its foundation; the way it was financed; the staffing and the use of volunteers and conscientious objectors to military service; the curriculum; and the pupils at the school-where they came from and their educational achievements.